The relationship between the concepts «innovation», «innovativeness» and «innovation activity» in the enterprise management system: the experience of the Polish researchers - V.V. Ksendzuk; A.D. Saakian (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
1 (39). – Р. 60–66: ill. 2. – Table 2. – Refs.: 24 titles. The article analyzes the conceptual apparatus in terms of management of innovative activity of enterprises. The feasibility for the relevance of research is carried out on the basis of analysis of statistical data in the sphere of use of innovations in the Ukrainian and Polish businesses. The research studied different approaches of Polish scientists to the interpretation of the concepts «innovation», «innovativeness» and «innovation activity» to justify the interdependence among them in theoretical and practical terms. This allowed to draw conclusions in terms of improvement of the studied concepts. Indeed, as shown by a study in entrepreneurial activities and in the scientific literature, approach to the interpretation of these concepts differs and requires revision with the aim of developing the theoretical foundations for the preparation of innovative business strategies, evaluation of indicators of innovativeness for stakeholder groups.